2001
DOI: 10.1021/ma001809z
|View full text |Cite
|
Sign up to set email alerts
|

Rubber-Modified Glassy Amorphous Polymers Prepared via Chemically Induced Phase Separation. 1. Morphology Development and Mechanical Properties

Abstract: The introduction of rubbery particles can be applied to enhance shear yielding and, consequently, the toughness of brittle amorphous polymers. The critical transition in these polymers from crazing to shear yielding requires a submicrometer-or even nanometer-sized rubbery phase. These can be obtained via coalescence suppression in processes involving chemically induced phase separation but are also obtained in interpenetrating polymer networks (IPN) where cross-linking or gelation is responsible for the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…This was inspired by synchrotron experiments on a similar system, PMMAaliphatic epoxy blends with extremely small structures in the order of 30 nm. [56][57][58][59] Under low speed testing ductile behavior was found since the material was able to initiate voids within the rubbery domain prior to shear yielding. Under high loading rates, realized by notching the sample, the material behaved brittle and no cavitation occurred.…”
Section: Results Of Analyses Of Improved Microstructuresmentioning
confidence: 99%
“…This was inspired by synchrotron experiments on a similar system, PMMAaliphatic epoxy blends with extremely small structures in the order of 30 nm. [56][57][58][59] Under low speed testing ductile behavior was found since the material was able to initiate voids within the rubbery domain prior to shear yielding. Under high loading rates, realized by notching the sample, the material behaved brittle and no cavitation occurred.…”
Section: Results Of Analyses Of Improved Microstructuresmentioning
confidence: 99%
“…The incorporation of precavitated, adhering core-shell rubbers, as proposed by Refs. [17,30], could support these ligaments during deformation to transfer more load. As a result they would be able to induce sequential yielding throughout the RVE, increase the material volume participating in the deformation and hence further improve the toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results provided by Van der Sanden [28] and Jansen [30] showed that a BDT occurs in non-adhering core-shell rubber filled polystyrene at 55 vol.% inclusions of 200 nm and 35 vol.% inclusions of 80 nm, respectively. In Jansen's example a critical inter-particle distance of 11.5 nm is found.…”
Section: Bdt Induced By Length-scale Effectsmentioning
confidence: 99%
“…17 PMMA have been toughened successfully by incorporating rubber particles. 18 They achieved superior toughness values with the average particle size of 50 nm in 70:30 PMMA/rubber blend. Blends of PMMA with polyethylene terephthalate (PET) was studied by Kamata et al, 19 and their results shows good processability and high impact strength.…”
Section: Introductionmentioning
confidence: 91%